Synoptic weather and surface ozone concentration in South Korea - Kim, Hyun Cheol; Lee, Dasom; Ngan, Fong; Kim, Byeong Uk; Kim, Soontae; Bae, Changhan; Yoon, Jin Ho (Atmospheric Environment, 2021)
Seventeen years (2001–2017) of surface observations and spatial synoptic classification (SSC) data are used to analyze the characteristics of surface ozone concentration according to synoptic weather patterns. While weather conditions are known to play an important role in regional air quality, the extent to which synoptic weather patterns affect the production of high ground-level ozone concentrations has not yet been fully quantified. Using thermal characteristics and geographic origins, the SSC method classifies air masses into six types: dry polar (DP), dry moderate (DM), dry tropical (DT), moist polar (MP), moist moderate (MM), and moist tropical (MT). We link daily maximum 8-h ozone concentrations (MDA8 O3) from 306 monitoring sites to the closest SSC classifications at 17 airport sites and then analyze their association. We find that DM, DT, and MT are commonly associated with high ozone, whereas DT produces ozone with the greatest efficiency, especially high levels of concentration. This finding implies a potentially strong connection between surface ozone and climate change because the occurrence of DT weather has increased by more than three times over the past 50 years in South Korea. Sensitivity tests reveal that mean MDA8 ozone may increase by 3.5% (7.5%) as the DT frequency increases by 200% (300%). The impacts are larger for higher levels of concentration, with 31.7% (63.3%) or more prevalence of the >80 ppb range with the same increased DT frequency. We conclude that synoptic weather and its long-term trends play important roles in the increased surface ozone recently seen in South Korea.
Keywords: Ground level ozone concentration; Ozone concentration; Regional air quality; Spatial synoptic classification; Surface observation; Surface ozone concentrations; Synoptic weather patterns; Thermal characteristics; Climate change; Ozone; Spatial synoptic classification; Synoptic weather